2016
DOI: 10.1186/s12943-016-0505-7
|View full text |Cite
|
Sign up to set email alerts
|

ERK mediated upregulation of death receptor 5 overcomes the lack of p53 functionality in the diaminothiazole DAT1 induced apoptosis in colon cancer models: efficiency of DAT1 in Ras-Raf mutated cells

Abstract: Backgroundp53 is a tumour suppressor protein that plays a key role in many steps of apoptosis, and malfunctioning of this transcription factor leads to tumorigenesis. Prognosis of many tumours also depends upon the p53 status. Most of the clinically used anticancer compounds activate p53 dependent pathway of apoptosis and hence require p53 for their mechanism of action. Further, Ras/Raf/MEK/ERK axis is an important signaling pathway activated in many cancers. Dependence of diaminothiazoles, compounds that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…At the same time, the other stated studies with similar findings do not give any clear explanation. To justify our finding of p-ERK activation upon AE-mediated PDT, we would agree with a postulation that ERK activation may depend on the cell type and the duration of phototherapy [39]. We thus report that AEmediated PDT leads to activation of p-ERK on BCC.…”
Section: Discussionsupporting
confidence: 87%
“…At the same time, the other stated studies with similar findings do not give any clear explanation. To justify our finding of p-ERK activation upon AE-mediated PDT, we would agree with a postulation that ERK activation may depend on the cell type and the duration of phototherapy [39]. We thus report that AEmediated PDT leads to activation of p-ERK on BCC.…”
Section: Discussionsupporting
confidence: 87%
“…5 and 6). Recent reports have also revealed that Akt, ERK and JNK can mediate DR upregulation (53)(54)(55). The findings of this study suggested that luteolin induced JNK activation via DR upregulation (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that some clinically used drugs make cancer cells sensitive to TRAIL by increasing the protein level of TRAILR1 and TRAILR2 [39]. Previous studies have shown that DAT1, one of the diaminothiazole drugs known to have antimitotic effects on colon cancer cells (HCT-116), activates the MEK/ERK signaling pathway, increasing the expression of the TRAILR2 receptor independent of p53.…”
Section: Discussionmentioning
confidence: 99%